Galectin 3 induces a distinctive pattern of cytokine and chemokine production in rheumatoid synovial fibroblasts via selective signaling pathways - Filer, Andrew D. (2009)
High expression of galectin 3 at sites of joint destruction in rheumatoid arthritis (RA) suggests that galectin 3 plays a role in RA pathogenesis. Previous studies have demonstrated the effects of galectins on immune cells, such as lymphocytes and macrophages. This study was undertaken to investigate the hypothesis that galectin 3 induces proinflammatory effects in RA by modulating the pattern of cytokine and chemokine production in synovial fibroblasts. Matched samples of RA synovial and skin fibroblasts were pretreated with galectin 3 or tumor necrosis factor alpha (TNFalpha), and the levels of a panel of cytokines, chemokines, and matrix metalloproteinases (MMPs) were determined using enzyme-linked immunosorbent assays and multiplex assays. Specific inhibitors were used to dissect signaling pathways, which were confirmed by Western blotting and NF-kappaB activation assay.